2016
DOI: 10.1108/md-02-2015-0052
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of open innovation on firm performances

Abstract: Purpose – The purpose of this paper is to explore the relationships between the openness of firms and their innovation and financial performances. Design/methodology/approach – In order to investigate such relationships, data on inbound and outbound open innovation (OI) processes and performances of 110 worldwide top research and development (R & D) spending bio-pharmaceutical companies are collected via the consolidated ann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
99
1
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(116 citation statements)
references
References 44 publications
6
99
1
10
Order By: Relevance
“…Second, regarding the relationship between open innovation strategy and firm performance, our findings are supported by Dries et al (), who concluded that firm openness is related to firm performance measured by turnover, and Caputo et al (), who found that sales growth shows a positive trend with openness. Moreover, similar to Dangelico, Pontrandolfo, and Pujari (), we differentiated between the collaboration in the inbound phase of eco‐innovation with agents inside and outside the supply chain.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Second, regarding the relationship between open innovation strategy and firm performance, our findings are supported by Dries et al (), who concluded that firm openness is related to firm performance measured by turnover, and Caputo et al (), who found that sales growth shows a positive trend with openness. Moreover, similar to Dangelico, Pontrandolfo, and Pujari (), we differentiated between the collaboration in the inbound phase of eco‐innovation with agents inside and outside the supply chain.…”
Section: Discussionsupporting
confidence: 82%
“…Some empirical studies highlight the importance of openness. Caputo, Lamberti, Cammarano, and Michelino () note that sales growth shows a positive relationship with firm openness. Furthermore, this openness is greater when the search for external knowledge is broader, that is, the higher the number of external sources on which a firm relies (Laursen & Salter, ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…One of the differences between open and closed innovation is that in previous theorizing of innovation, external knowledge played useful but complement role [28]. But in open innovation, external knowledge plays a role corresponding to what is achieved from internal knowledge in previous conceptualizing [29].…”
Section: Theoretical Underpinningsmentioning
confidence: 97%
“…It should be noted that the grounded theory research is usually applied in cases where the subject suffers a lack or little attention in previous studies [28] with an open innovation approach for the insurance industry?" It is recommended that a review of the study be conducted by members and peers in order to ensure the research validity and accuracy of findings [28]. In the present study, it is sought the same way for review and validity.…”
Section: Methodsmentioning
confidence: 99%
“…Open innovation has gained popularity in recent years due to several studies in the literature which concur that this construct can be classified as one of the most important performance drivers for many companies (Hauser et al, 2006;Lichtenthaler, 2009;Lee, Park, Yoon, & Park, 2010;Mazzola, Bruccoleri, & Perrone, 2012;Chaston, 2013;Kuang-Peng & Chou, 2013;Caputo, Lamberti, Cammarano, & Michelino, 2016;Casprini, De Massis, Di Minin, Frattini, & Piccaluga, 2017;Park & Kwon, 2018). The concept is wideranging; it can be defined as a new set of forms that serve as a model in innovation administration (Gassmann, 2006), it uses sources of internal and external knowledge that help in the acceleration of innovation (Van de Vrande, De Jong, Vanhaverbeke, & De Rochemont, 2009), and it involves procedures related to external collaboration and cooperation to promote the growth and development of new products or technologies (Freel, 2006).…”
Section: Theoretical Frameworkmentioning
confidence: 99%